2023
DOI: 10.1186/s12873-023-00896-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating PCSK9 level is associated with 28-day mortality in patients with sepsis: a prospective cohort study

Yuanlu Shu,
Ziwei Deng,
Ye Deng
et al.

Abstract: Objectives Pro-protein convertase subtilisin/kexin 9 (PCSK9) decreases the clearance of the pathogenic lipids, supporting the potential role of PCSK9 in the prognosis of sepsis. Methods In this prospective cohort study, patients with sepsis were consecutively recruited from 1 to 2020 to 30 September 2021 at the First People’s Hospital of Huaihua, China. All the eligible patients were categorized into low-PCSK9 and high-PCSK9 groups, based on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that subjects with at least one loss of function (LOF) PCSK9 allele were more likely to survive, whereas subjects carrying the gain-of-function (GOF) allele were less likely to survive 26 . Moreover, a study by Shu and his coworkers in 2023 reported that the 28-day mortality of sepsis increased significantly as the baseline circulating PCSK9 level exceeded 370 ng/ml in their patients, indicating circulating PCSK9 levels may be a potential biomarker to predict the prognosis of sepsis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that subjects with at least one loss of function (LOF) PCSK9 allele were more likely to survive, whereas subjects carrying the gain-of-function (GOF) allele were less likely to survive 26 . Moreover, a study by Shu and his coworkers in 2023 reported that the 28-day mortality of sepsis increased significantly as the baseline circulating PCSK9 level exceeded 370 ng/ml in their patients, indicating circulating PCSK9 levels may be a potential biomarker to predict the prognosis of sepsis 29 .…”
Section: Discussionmentioning
confidence: 99%